Building Filipino Hawai'i - Labrador, Roderick N. (Book collections on Project MUSE., 2015)
"Drawing on ten years of interviews and ethnographic and archival research, Building Filipino Hawai'i delves into the ways Filipinos in Hawai'i have balanced their pursuit of upward mobility and mainstream acceptance with a desire to keep their Filipino identity."--